Burning Mouth Syndrome: Aetiopathogenesis and Principles of Management - L. Feller; J. Fourie; M. Bouckaert; R. A. G. Khammissa; R. Ballyram; J. Lemmer (Pain Research and Management)
Burning mouth syndrome (BMS) is a chronic debilitating oral condition characterised by a burning sensation of the oral mucosa in an otherwise apparently normal person. Its aetiology and pathogenesis are obscure, but both psychogenic factors and peripheral and central neuropathies appear to be implicated. There is no cure for BMS, and treatment with either local or systemic medications focuses on the relief of symptoms and on improving quality of life. In recalcitrant cases, psychological/psychiatric intervention may be helpful. In order to improve treatment outcomes, a better understanding of the pathogenesis of this syndrome might provide a basis for the development of more effective management strategies. In this short review, we discuss current knowledge of the diagnosis, aetiopathogenesis, and management of BMS.